FORMULASI STRATEGI KANTOR AKUNTAN PUBLIK DI INDONESIA: PENERAPAN ANALISIS SWOT DAN ANALYTICAL HIERARCHY PROCESS DALAM MENGHADAPI ASEAN ECONOMIC COMUNITYV&N PERSAINGAN GLOBAL - , Tarkosunaryo ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Public accountant in Indonesia is one of the important pillars of the economy, that is, as an independent party that provide assurance services to enhance the credibility and quality of the financial information presented by an entity. Law No. 5 of 2011 provides legal backing for public accountants in Indonesia, including exclusivity rights on assurance services that can only be provided by a public accountant. Public Accountant is a global profession considering that various issues in this profession have been determined to using the criteria and standards globally. Auditing standards, code of ethic, and financial reporting standards in Indonesia has been revised to adopt international standards locally as such standards. Adoption of the international standards also has been conducting by many countries in other parts of the world so that the profession is likely borderless territorial limits as a country. Similarly, in the ASEAN region, countries leaders have agreed on the liberalization of services in this region by 2015, including accounting services area. The purpose of this study is to identify SWOT factors, namely strengths, weaknesses, opportunities, and threats of the external and internal environment of the public accountants in Indonesia that provide results to determine the priorities of the strategy. The ultimate result of this research is a formulation of some alternative strategies that can be applied to public accountants in Indonesia to improve competitiveness and achieving the competitive advantages in ASEAN Economic Community 2015 and global competition. This study uses a qualitative method by using SWOT analysis approach and the analytical hierarchy process (AHP). This research also applied the validity and relevance statistical tests to improve quality of the SWOT factors. While AHP is applied to determine the priority weight of each SWOT factors in formulating strategic alternatives. Unit of analysis in this study is public accountant profession in Indonesia as an industry.